STED microscopy visualizes energy deposition of single ions in a solid-state detector beyond diffraction limit. (5th April 2017) - Niklas, M; Henrich, M; Jäkel, O; Engelhardt, J; Abdollahi, A; Greilich, S
Abstract: Fluorescent nuclear track detectors (FNTDs) allow for visualization of single-particle traversal in clinical ion beams. The point spread function of the confocal readout has so far hindered a more detailed characterization of the track spots—the ion's characteristic signature left in the FNTD. Here we report on the readout of the FNTD by optical nanoscopy, namely stimulated emission depletion microscopy. It was firstly possible to visualize the track spots of carbon ions and protons beyond the diffraction limit of conventional light microscopy with a resolving power of approximately 80 nm (confocal: 320 nm). A clear discrimination of the spatial width, defined by the full width half maximum of track spots from particles (proton and carbon ions), with a linear energy transfer (LET) ranging from approximately 2–1016 keV µ m −1 was possible. Results suggest that the width depends on LET but not on particle charge within the uncertainties. A discrimination of particle type by width thus does not seem possible (as well as with confocal microscopy). The increased resolution, however, could allow for refined determination of the cross-sectional area facing substantial energy deposition. This work could pave the way towards development of optical nanoscopy-based analysis of radiation-induced cellular response using cell-fluorescent ion track hybrid detectors.